The pet and the pendulum - McAlpine, Gordon (McAlpine, Gordon. Misadventures of Edgar & Allan Poe, 2016)
Back in Baltimore, twelve-year-old identical twins Edgar and Allan think they have encountered the ghost of their great-great-great-great granduncle, Edgar Allan Poe, asking them to solve his murder--but really it is their arch-nemesis, Professor Perry, looking for revenge.